Estrategias lúdicas para el control de emociones en los niños de Preparatoria de la Escuela de Educación Básica “Fe y Alegría” de la ciudad de Riobamba. - Ashqui Chafla, Kely Dayana (2024)
The main objective of this research study entitled " Estrategias Lúdicas para el control de emociones en los niños de Preparatoria de la Escuela de Educación Básica Fe y Alegría" School of Basic Education, has as its general objective to establish playful strategies for the control of emotions in high school children in the aforementioned educational institution. To achieve this purpose, a methodology with a quantitative approach has been employed, using a nonexperimental design and a bibliographic type level. In this way, it was configured as a field study, which allowed us to obtain reliable data from the real context of the institution, to obtain the data we used the observation technique, focusing on how the game helped the children to express and control their emotions. For this purpose, an observation sheet with specific indicators was elaborated, which made it possible to evaluate the behavior and development of the child in relation to the subject of the study. The results obtained through observation revealed that the use of interactive activities in the emotional development of children helps them to be more confident and free to say what they feel. However, it can be seen that the teacher is an active agent of emotional development and should make consistent use of these skills. Based on the analysis of the results, a set of interactive activities has been developed so that children can explore and experience each emotion in different situations. It is important to highlight that this research contributed greatly to the educational and social sphere, by providing recommendations that can be of great use in the integral development of children as well as guaranteeing an education for life.